A base de cálculo do Imposto sobre a Propriedade de Veículos Automotores usados: medida de praticabilidade tributária e um caso de inconsistência da regra-matriz de incidência tributária causada pelo descompasso entre os critérios temporal e quantitativo - Souza, José Carlos Cardoso (2022)
The calculation of the IPVA calculation basis, when the incidence is on used vehicles, is provided for by the laws in procedures that determine the search for the market value of these vehicles, which constitutes a measure of Tax Practicability, but can compromise the soundness of the Rule - Tax Incidence matrix if it causes a mismatch between its criteria. There are studies dealing with the Tax Incidence Matrix Rule as a scientific instrument capable of facilitating the organization of the statement that deals with the tax incidence; and others that deal with Tax Practicability as a measure to simplify compliance and application of tax laws, but there is a lack of studies dealing with the need for alignment between the criteria of the Tax Incidence Matrix Rule; and also studies comparing Tax Practicability norms with tax incidence norms, with a view to detecting the influences of these on the former as a possible cause of that misalignment between the criteria. The objective of the present work is to make this comparison, in order to determine whether those norms of Tax Practicability, contained in the laws governing the IPVA, cause any reflection in the Matrix Rule of Tax Incidence, to the point of causing a misalignment between its criteria. To this end, the IPVA governing laws of all taxing entities were selected as the object of research, submitting them to a careful analysis of their statements that deal with the temporal criterion and the quantitative criterion, with an exclusive focus on the procedure for setting the calculation basis in the incidence on used motor vehicles. The result was the confirmation of the Incidence Matrix Rule, as a skillful scientific instrument for in-depth analysis of the tax incidence rule, and as a consequence, also to highlight the reflexes caused in the incidence rule by the Tax Practicability rules and, finally, that the calculation base calculation rules on the incidence of IPVA of used vehicles is the cause of mismatch between the temporal and quantitative criteria of the incidence matrix rule